2016
DOI: 10.1002/pssc.201510187
|View full text |Cite
|
Sign up to set email alerts
|

Effect of QW growth temperature on the optical properties of blue and green InGaN/GaN QW structures

Abstract: In this paper we report on the impact that the quantum well growth temperature has on the internal quantum efficiency and carrier recombination dynamics of two sets of InGaN/GaN multiple quantum well samples, designed to emit at 460 and 530 nm, in which the indium content of the quantum wells within each sample set was maintained. Measurements of the internal quantum efficiency of each sample set showed a systematic variation, with quantum wells grown at a higher temperature exhibiting higher internal quantum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 23 publications
4
11
0
Order By: Relevance
“…Nevertheless, the relative emission efficiency of the samples is consistent with expectations, i.e., at all of the N 0 ’s studied, it increases with T G , consistent with the lower incorporation of point defects at higher growth temperatures. The relative performance of the three samples shown in Figure a is also consistent with the IQE values reported previously in the literature at lower excitation rates. However, what is most notable is the remarkable similarity of the behavior of the three samples at high N 0 values (>1 × 10 19 cm –3 ), which is most readily evident when comparing normalized versions of the droop curves, as shown in Figure b.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…Nevertheless, the relative emission efficiency of the samples is consistent with expectations, i.e., at all of the N 0 ’s studied, it increases with T G , consistent with the lower incorporation of point defects at higher growth temperatures. The relative performance of the three samples shown in Figure a is also consistent with the IQE values reported previously in the literature at lower excitation rates. However, what is most notable is the remarkable similarity of the behavior of the three samples at high N 0 values (>1 × 10 19 cm –3 ), which is most readily evident when comparing normalized versions of the droop curves, as shown in Figure b.…”
Section: Resultssupporting
confidence: 90%
“…This relative emission efficiency can be used as a proxy for IQE even though, as shown below, it is proportional to the IQE time-averaged over the decay of the carrier density. Each of the samples, described in detail in the Methods section, is labeled by its QW growth temperature, T G , in °C, which has previously been shown for these samples to inversely correlate with increased SRH recombination and so is consistent with a positive correlation with point defect density . Our previous studies also revealed that the emission efficiency measured in this way under identical experimental conditions can exhibit significant point-to-point variation across the sample, in a similar way to other reports that attributed it to the effect of step edges on local point defect density .…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…First, the indium incorporation is sensitive to the growth conditions, such as growth temperature, growth rate, V/III ratio 6 , and the hydrogen flow rate 7 . In addition, the growth temperature of InGaN should be much lower than GaN due to the low dissociation temperature of InN 8 . In fact, the growth of InGaN epilayer has to be performed at temperature range of 650–850 °C.…”
mentioning
confidence: 99%